Michel Houellebecq’s Submission – a novel of decadence - Bikulčius, Vytautas (Literatūra, 2019)
Michel Houellebecq’s Submission has been analysed as a novel of decadence in this paper. Referring to the works of Michel Winock, François Livi and Michel Onfray, it has been found that a decadent novel can be associated not only with the works of Joris-Karl Huysmans, Pierre Loűys, Jean Lorrain and others produced at the end of the 19th century but also at subsequent periods. Such characteristics of decadent writing as the threat of catastrophe, fundamental changes in society, nostalgia can be found in the analysed novel.François, the main character of the novel, an expert on Huysmans and a professor at Sorbonne University, supports Huysmans’ ideas to some extent trying to find the link between the end of the 19th century and the beginning of the 21st century by comparing processes in society. Huysmans sought an ideal in the Middle Ages, while François travels to Rocamadour, famous for the statue of the Black Madonna, with a hope to find a spiritual revelation but becomes aware that the world of the past has gone forever. Changes in society made Huysmans leave the monastery, similarly, François gets frustrated as he loses his job when the Muslim Fraternity comes into power.Using the dystopian genre, Houellebecq depicts unbelievable changes in society – the new government proclaims Islam an official religion of France. Society is governed by new rules, the authority is concerned about two things – demography and education. Those, who refuse to convert to Islam, lose their jobs. Changes in society are even linked with geopolitical changes. Meanwhile Houellebecq reveals significant differences between the decadence of the end of the 19th and of the 21st century. Huysmans’ decadence results in neuroses, a desire to seal himself off from the world in alcohol, drugs, etc., to surround himself with works of art, while François in Submission enjoys erotic pleasures, gradually becomes an alcoholic, he does not suffer like Huysmans’ protagonist Des Esseintes. It can be stated that Submission is a decadent novel only at thematic level since aesthetic values, characteristic of the decadence of the 19th century, are left in the background. The only justification of François is that he speaks about his conversion to Islam hypothetically, it shows that he has not made up his mind to take this step.
Keywords: Houellebecq; decadence; Huysmans; neurosis; dystopia